The Mediating Effect of Emotion on Consumer Purchase Behavior in E-commerce Live Streaming Based on the S-O-R Model - Wang, Qi; Musa, Rosidah Binti (International Journal of Global Economics and Management, 2024)
In the era of Media 3.0, brands and merchants are increasingly utilizing e-commerce live streaming as a key strategy for engaging consumers in an interactive and immersive digital environment. One critical factor in this engagement is the emotional transmission to consumers, which plays a pivotal role in influencing their participation and purchasing behavior. E-commerce live streaming presents a unique blend of real-time communication, social interaction, and commercial transactions, making it essential to understand the underlying psychological mechanisms at play. This study, grounded in the Stimulus-Organism-Response (S-O-R) model, investigates how emotional responses, triggered by stimuli such as product presentation, anchor credibility, and peer feedback, mediate the relationship between the live-streaming environment and consumer purchasing decisions. By examining the impact of both positive and negative emotions, this research aims to uncover the emotional pathways that drive consumer engagement and purchase intentions in the live streaming context. The findings not only contribute to the theoretical understanding of emotional mediation in digital commerce but also provide practical insights for enhancing live-stream marketing strategies to optimize consumer behavior outcomes.